1998
DOI: 10.1161/01.hyp.31.2.627
|View full text |Cite
|
Sign up to set email alerts
|

Diabetic Nephropathy Is Associated With AGT Polymorphism T235

Abstract: Abstract-Diabetic nephropathy is a serious and frequent complication of insulin-dependent diabetes mellitus (IDDM) that has a strong genetic component. Several case-control studies have reported conflicting results with regard to the role of angiotensinogen gene polymorphisms, specifically the M235T T allele, in the development of diabetic nephropathy. The primary limitation of the case-control approach is that bias may be introduced by unrecognized differences in the populations selected for cases and control… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
30
2

Year Published

1998
1998
2012
2012

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 61 publications
(35 citation statements)
references
References 24 publications
3
30
2
Order By: Relevance
“…54,55 However, we could find no association of GFR and plasma active renin with these ACE and angiotensinogen polymorphisms or those of the renin gene. Our results do not exclude small phenotypic effects of these polymorphisms or the involvement of other polymorphisms of these or other genes.…”
Section: Discussioncontrasting
confidence: 55%
“…54,55 However, we could find no association of GFR and plasma active renin with these ACE and angiotensinogen polymorphisms or those of the renin gene. Our results do not exclude small phenotypic effects of these polymorphisms or the involvement of other polymorphisms of these or other genes.…”
Section: Discussioncontrasting
confidence: 55%
“…The RAS is a strong candidate as prior studies have demonstrated a more consistent association between ACE and Atg gene variants with the progression of renal insufficiency in various renal diseases, compared to the initiation of renal inflammation. [24][25][26][27] The results of this study suggest that DNA sequence variation in the ACE and Atg genes significantly influences the rate of progression of renal disease, and potentially survival, in LN patients. Previous studies in LN have been limited to the ACE I/D polymorphism, and have yielded highly discordant results.…”
Section: Discussionmentioning
confidence: 76%
“…The design of this study allows us to investigate the role of candidate genes involved in diabetic nephropathy susceptibility within these families without the effects of confounding due to population stratification. The use of families with a Type I diabetic offspring without nephropathy allows us to exclude excess transmission that may be seen at a Type I diabetes susceptibility locus [16]. Since we have observed no significant deviation in either families with or without diabetic nephropathy, we are confident that transmission of alleles at this polymorphism do not contribute substantially to nephropathy risk.…”
Section: Discussionmentioning
confidence: 84%
“…The role of candidate genes can also be assessed in family-based association studies [15]. We have recently reported, for the first time, the use of such a family association study in assessing candidate genes in diabetic nephropathy susceptibility [16]. The basis of this study is the transmission disequilibrium test (TDT), a powerful method to assess susceptibility alleles in the causation of polygenic disease [15,17].…”
Section: : 1304±1308]mentioning
confidence: 99%
See 1 more Smart Citation